HUBUNGAN ANTARA RASA PERCAYA DIRI DENGAN KEMAMPUAN BERBICARA PADA SISWA KELAS V DAN VI SEKOLAH DASAR - Aisa Ointu; Ansar Ansar; Thamrin A. Kum (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
ABSTRACT Starting from the importance of developing elementary students’ speaking skills, which are influenced by psychological factors, particularly self-confidence, this study aims to determine the level of students’ self-confidence, their speaking ability, and the relationship between self-confidence and speaking ability among fifth and sixth grade students at SD Laboratorium UNG. This study aims to determine the level of students’ self-confidence, speaking ability, and the relationship between self-confidence and speaking ability in fifth and sixth grade students at UNG Laboratory Elementary School. This study used a quantitative approach with a correlational design. The population of this study was all fifth and sixth grade students at UNG Laboratory Elementary School, with a sample size of 99 students. Data collection techniques used self-confidence questionnaires and speaking ability questionnaires that had been tested for validity and raliability. Data analysis techniques included descriptive and inferential analysis, consisting of normality tests, linearity tests, correlation tests, and significance tests. The results of the study showed that the level of students’ self-confidence was in the high cateegory, and students’ speaking ability was in the médium category. The results of the correlation analysis indicate a significant rrelationship between self-confidence and students’ speaking ability, with a contribution of 48,44%. Therefore, it can be concluded that self-confidence plays a crucial role in improving students’ speaking ability. ABSTRAK Berangkat dari pentingnya pengembangan kemampuan berbicara siswa sekolah dasar yang dipengaruhi oleh faktor psikologis, khususnya rasa percaya diri, penelitian ini bertujuan untuk mengetahui tingkat rasa percaya diri siswa, kemampuan berbicara siswa, serta hubungan antara rasa percaya diri dengan kemampuan berbicara pada siswa kelas V dan VI SD Laboratorium UNG. Penelitian ini bertujuan untuk mengetahui tingkat rasa percaya diri siswa, kemampuan berbicara siswa, serta hubungan antara rasa percaya diri dengan kemampuan berbicara pada siswa kelas V dan VI SD Laboratorium UNG. Penelitian ini menggunakan pendekatan kuantitatif dengan desain korelasional. Populasi penelitian ini adalah seluruh siswa kelas V dan VI SD Laboratorium UNG dengan jumlah sampel sebanyak 99 siswa. Teknik pengumpulan data menggunakan angket rasa percaya diri dan angket kemampuan berbicara yang telah diuji validitas dan reliabilitasnya. Teknik analisis data meliputi analisis deskriptif dan analisis inferensial yang terdiri uji normalitas, uji linier dan linearitas, uji korelasi, dan uji signifikan. Hasil penelitian menunjukkan bahwa tingkat rasa percaya diri siswa berada pada kategori tinggi, dan kemampuan berbicara siswa berada pada kategori sedang. Hasil analisis korelasi menunjukkan bahwa terdapat hubungan yang signifikan antara rasa percaya diri dengan kemampuan berbicara siswa ditunjukkan dengan kontribusi sebesar 48,44%. Dengan demikian dapat disimpulkan bahwa rasa percaya diri memiliki peranan penting dalam meningkatkan kemampuan berbicara siswa.